The Relationship Between Self-Control and Learning Independence During the Covid-19 Pandemic - Wahyu Adjie; Leni Armayati; Irfani Rizal (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Independent learning is a form of desire and a sense of being able to learn on one's own accord, whether in the presence or absence of other people, to decide learning goals in terms of knowledge, skills, and attitudes in solving problems. Individuals who have good learning independence will have good self-control so that they can control their actions both consciously and unconsciously. This study aims to determine the relationship between self-control and learning independence during the Covid-19 pandemic in SMA Negeri 4 Pekanbaru students. This study involved 123 students of SMA Negeri 4 Pekanbaru who were selected using a stratified random sampling technique. The measuring tool used in this study is the self-control scale, which consists of 16 items compiled by Sari (2022). And the learning independence scale totals 11 items compiled by Sari (2022). Data analysis used the Spearman Rho correlation analysis technique, the results of the analysis test obtained a coefficient of r = 0.053. This explains that there is an insignificant positive relationship between self-control variables and learning independence in SMA Negeri 4 Pekanbaru students.